IMPLEMENTASI MEDIA PEMBELAJARAN PENGENALAN JARINGAN KOMPUTER DENGAN ADOBE FLASH CS 3 PROFESSIONAL - Ariansyah -; Nurmayanti -; Gardini Emsco Sumbadri (IIB Darmajaya, 2019)
In the world of education today the role of computers has become very much needed, almost all schools have used computer aids for administrative processes and other matters. This research is motivated by the lack of use of computers as a learning medium in SMK Negeri 1 Prabumulih, the delivery and explanation of the material still use previous methods such as, using books and explaining on the board. The purpose of this research is to make the Application of Learning Media for Introduction to Computer Networks for Multimedia students using Adobe Flash CS 3 Professional. The results of research in making instructional media are carried out through a process of analysis, production design, implementation, and evaluation. In the analysis process, edutainment aspects that must be present in the learning media are obtained, including an attractive, interactive display, using sound effects, pictures and videos of learning material. Furthermore, the learning media are packaged in a CD. So hopefully with this learning media, the learning system at SMK Negeri 1 Prabumulih can be even better.Keywords - Learning Media, Multimedia, Computer Network